Kualitas Layanan Dan Program Kerja Terhadap Retensi Pelanggan Di Apotek - Putri, Hesti Nursari; Wahyono, Djoko; Hapsari, Indri (Syntax Literate, 2025)
Customer retention is a key performance indicator in the pharmaceutical service sector, especially amid rising competition and increasingly complex customer needs. This study aims to examine the effect of service quality and work programs on customer retention in pharmacies. Service quality dimensions analyzed include reliability, responsiveness, assurance, empathy, and tangible evidence. Work programs involve health education, loyalty programs, and customer relationship management. This research adopts a quantitative approach with a survey method targeting active pharmacy customers who have used the service at least three times in the past six months. Data were analyzed using multiple linear regression. Results reveal that both service quality and work programs significantly and positively influence customer retention, with empathy and responsiveness being the most dominant dimensions. These findings imply the need to improve service quality and develop proactive work programs such as health counseling and rewards for loyal customers. This study contributes theoretically to the development of retention strategies in the pharmaceutical sector and provides practical guidance for pharmacy managers.